Pneumonitis secondary to intravesical Bacillus-Calmette-Guérin (BCG) immunotherapy - Komeil Alattar, MBBS, PGCert; Sagar Dodhia, MBBS, BSc, PGCert; Michael Levi, MD (Radiology Case Reports, 2025)
Intra vesical Bacillus Calmette-Guérin (BCG) instillation therapy is a well-established treatment for superficial bladder cancer, though it can occasionally lead to rare systemic complications. We report the case of a man in his early 80s who developed acute onset dyspnoea after receiving BCG therapy. Clinical evaluation supported by pathology and multi-modal imaging including X-rays, CTs and PET scans led to a diagnosis of BCG-induced pneumonitis, a rare but serious complication. The exact underlying mechanism is still not fully understood and thus no standardized treatment protocol exists. Success has been reported in the literature with the use of anti-tuberculous drugs in combination with steroids. Our patient was successfully treated with anti-tuberculous medication only, for 4 months. This case highlights the importance of maintaining awareness for systemic BCG findings in patients undergoing intra vesical BCG instillations.